Effects of fractal grid on spray characteristics and flame development in burner combustion - Amirnordin, Shahrin Hisham; Khalid, Amir; Suardi, Mirnah; Manshoor, Bukhari; Hushim, M F (IOP Publishing, 2017)
Turbulence generator plays an important role in enhancing turbulence in combustion and determining the flame characteristics in burner combustion. This research demonstrated the effect of a fractal grid on the spray and flame characteristics in burner combustion. Three geometrical configurations of fractal grid were investigated with different equivalence ratios of 0.5–1.0. The images were captured using direct photographic method. The characteristics of the spray and flame were studied, including the length, angle, and area. The results from this fractal grid were compared with the swirl. The results showed that the fractal geometry and ratio of air-to-fuel mixture affected the performance of the burner. The correct combination of fractal geometry and air-to-fuel ratio resulted in complete combustion and improved the overall performance of the burner.